Costs related to obtaining organs for transplantation: A systematic review - Silva, Aline Moraes da (2022)
Introduction The number of transplants in the world is growing, although there is a demand that exceeds supply. It is worth mentioning that the costs for obtaining organs are considered high. However, few studies have been developed on analyzing the costs of obtaining organs and tissues for transplants in order to support the decision-making of managers and health professionals. Objective To summarize the studies related to the cost of obtaining organs for transplants from a deceased donor. Method A systematic literature review was conducted in the following databases: PubMed, Cochrane Library CINAHAL, Virtual Health Library (BVS), SCOPUS, Web of Science and EMBASE, using the following descriptors: Costs and cost analysis; Donor Selection; Tissue and Organ Procurement; Tissue and Organ Harvesting; and Tissue Donors, in studies published until April 2021. The risk of bias assessment was performed using the Joanna Briggs Institute's Checklist for Economic Assessments. It was not possible to perform a meta-analysis due to the heterogeneity of the studies. Results A total of 1731 studies were identified, of which 11 were analyzed. The cost of kidneys in US dollars (USD) ranged between USD $1672 and USD $25,058. Obtaining a liver ranged from USD $586 to USD $44,478. Heart procurement ranged from USD $633 to USD $24,264. The combined heart-lung transplant ranged from USD $860 to USD $23,203. Obtaining the pancreas ranged from USD $413 to USD $29,708. Conclusions Cost of obtaining organs for transplants from a deceased donor is substantial and varies widely across different studies. The overall cost of failures to obtain organs is currently unknown. Understanding organ procurement expenses can help clarify areas in which organ and tissue procurement can improve in cost and efficiency.